The comparison of loneliness in athlete and non-athlete women - Hemati-Alamdarloo, G.; Shojaee, S.; Asadmanesh, E.; Gholami, M.; Rahmani, H. (Journal of Human Sport & Exercise, 2019)
The aim of the present study was to compare the loneliness in athlete and non-athlete women. The statistical population of the present study included all athlete and non-athlete women in Shiraz, Iran. The sample consisted of 764 subjects (382 athletes, 382 non- athletes) that the athletes sample selected by Gerjesy and Morgan`sample size table and non-athletes sample selected by purposeful sampling method. Loneliness scale (Dehshiri et al., 2008) was used for measuring the loneliness. Independent t-test and multivariate analysis of variance (MANOVA) tests were used for data analysis. The results showed a significant difference between athlete and non-athlete females in the loneliness and its subscales (p<0/05). According to this finding, loneliness in athletes is less than non-athlete women. Regarding the findings of this study, it can be argued that sport activities play a role in reducing the loneliness of women.